The Role of Entrepreneurial Orientation on the Global Vegetable Supply Chain and on Farm Performance in West Java, Indonesia - Nunung Kusnadi; Etriya Etriya; Yanti N. Muflikh; Siti Jahroh; Herawati Herawati (School of Business, Bogor Agricultural University (SB-IPB), 2018)
Global market provides opportunities for business owners to grow their business. However, to what extent farmers – as one of business owners – take benefits from the global markers remains unclear. This paper aims to investigate the impact of entrepreneurial orientation on farmers’ involvement in global supply chain, in turn on farm performance. The data were gathered from a survey of 320 samples of vegetable farmers in three regions in West Java, Indonesia. Using PLS analysis, our findings demonstrate that farmers with higher entrepreneurial orientation (reflected by dimensions of innovativeness, proactiveness, risk taking, competitive aggressiveness, and autonomy), involve more in global supply chain, and gain higher farm performance. Ultimately, the more farmers involve in global supply chain, the higher their farm performance. Our findings provide an empirical support for the impact of entrepreneurial orientation on enabling farmers’ ability to involve in broader supply chains beyond the domestic ones. As a consequence, farmers enjoy better farm performance.